Web-based digital twin online laboratories: Methodologies and implementation - Lei, Zhongcheng; Zhou, Hong; Hu, Wenshan; Liu, Guo-Ping (Digital twin, 2022)
Background: Online laboratories that provide online experimentation are crucial for education and research in all fields of engineering. As a transformative technology, the digital twin can be potentially applied into online laboratories to enable physical-digital twin interactions and enhance user experience. Methods: In this article, web-based digital twin online laboratories are discussed, the methodologies and implementation of which are presented in detail. The digital twin architecture, three-dimensional twin model, web-based digital twin control algorithm design, and real-time physical-twin control are explored to provide a full picture for the design and implementation of digital twin online laboratory systems. To illustrate the effectiveness of the proposed methodologies, a use case with the Networked Control System Laboratory (a previously developed control and automation laboratory) is provided, which details the design and implementation. Results: A four-tier web architecture has been implemented. With the provided web interface, control algorithms can be designed and employed for real-time digital twin experimentation. The experimental results demonstrated that the physical-digital twin fan speed control system can achieve good control and tracking performance with human-in-the-loop interactions. Conclusions: This article presents the methodologies and implementation of digital twin web-based online laboratories. The use case verified the proposed web architecture, digital twin implementation, control architecture, and human-in-the-loop interactions for a digital twin experimentation system, which can potentially be used for the design and implementation of other digital-twin applications in different fields.